Expansionary Austerity : Reallocating Credit Amid Fiscal Consolidation - Morais, Bernardo (World Bank, Washington, DC, 2021)
This paper shows expansionary fiscal austerity via reallocation of credit supply, but with a raise in poverty. For identification, the paper exploits the introduction of a Mexican law limiting the debt of subnational governments along with matched credit register, firm, bank, and state datasets. After the law, states with higher ex ante public debt grow substantially faster, despite larger fiscal consolidation (higher taxes and lower public expenditure). Banks operating in more indebted states reallocate credit supply away from local governments into private firms, with stronger effects for banks with higher exposure to local public debt, consistent with lowering crowding out. Effects only happen after the law, not before, and there are strong firm-level real effects associated. The reduction of crowding out is stronger for financially constrained firms and for firms operating in states with higher ex ante public spending on social services over infrastructure projects. In states more affected by the law, despite better economic effects, extreme poverty increases––especially in states with higher ex ante public spending on social services over infrastructure––consistent with a strong reduction for social services during the fiscal consolidation.